Effective Partnerships Achieve Results : Client-focused ASAP Program Emphasizes Strategic Planning; Delivers Impressive Results Across the Region - Rodriguez-García, Rosalía; Bortman, Marcelo; Boccardi Vidarte, Andrea; Gaillard, Eric (World Bank, Washington, DC, 2012)
National AIDS strategy frameworks have become a mainstay of AIDS responses in countries affected by the epidemic. Faced with the challenge of responding to the changing epidemic in a context of growing needs and limited resources, governments have turned to evidence informed AIDS strategies as a tool for designing their national responses. National HIV/AIDS strategies must be carefully crafted, not only continuing a general focus on prevention and treatment, but also targeting narrower interventions as the epidemic evolves within regions or smaller at-risk groups in each country.